Руководство исследовательской деятельностью и её организация в вузе - Байкенова, Р.Т. (My University, 2013)
This article discusses three ways management research in the university, depending on the characteristics of the individual student. Just consider the use of various types of educational research, design and research activities as a form of research skills.